9.02.001: "Jamie Snider and Don Walsh, Demo 1976" - Snider, Jamie; Walsh, Don (1976)
In 1976 we were looking to make enough money to buy a small P.A. System. We got paid 800.00 for this gig (I believe it was Thu, Fri, Sat and Sun). We took the money and got our 800.00 P.A. In 1976 800.00 was big pay for a two-piece band. This was the start of Red Island. This is the demo tape we made for them. It was recorded on Vince MacCarthy's Harmon Kardon tape recorder.